Effects of different surface treatments and accelerated artificial aging on the bond strength of composite resin repairs - Melo,Marco Aurélio Veiga de (2011)
The purpose of the present study was to assess the bond strength of composite resin repairs subjected to different surface treatments and accelerated artificial aging. 192 cylindrical samples (CSs) were prepared and divided into 24 groups (n = 8). Half of the CSs were stored in water for 24 h, and the other half were subjected to C-UV accelerated aging for non-metallic specimens. The treatments were phosphoric acid + silane + adhesive (PSA); phosphoric acid + adhesive (PA); diamond bur + phosphoric acid + silane + adhesive (DPSA); diamond bur + phosphoric acid + adhesive (DPA); air abrasion + phosphoric acid + silane + adhesive (APSA); and air abrasion + phosphoric acid + adhesive (APA). The repair was performed and the specimens were again aged as described above. A control group (n = 8) was established and did not receive any type of aging or surface treatment. The specimens were loaded to failure in shear mode with a crosshead speed of 0.5 mm/min until fracture. Data were analyzed by one-way ANOVA/Tukey's test (p < 0.05). No statistically significant differences were found among DPSA, DPA, APSA, APA, and the control group. The aged PSA and PA achieved low bonding values and were statistically different from the control group, whereas the non-aged PSA and PA presented no statistically significant difference from the control group. Repairs with the proposed surface treatments were viable on both recent and aged restorations; however, phosphoric acid + adhesive alone were effective only on recent restorations.